Intimate betrayal : understanding and responding to the trauma of acquaintance rape - Wiehe, Vernon R. (Sage Publications, 1995)
Educates university and college personnel, counselors, clergy and teachers about the nature, scope, and impact of acquaintance rape on its victims, and methods of intervention and prevention. Survivors describe events in their own words in chapters on typical assault settings, marital rape, legal aspects of acquaintance rape, the counselor and the.